2020
DOI: 10.2196/15098
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Mobile Texting App (HepTalk) in Encouraging Patient Participation in Viral Hepatitis B Care: Development and Cohort Study

Abstract: Background Chronic hepatitis B virus (HBV) infection is a major cause of liver-related morbidity and mortality among Asian Americans in the United States. Despite the available resources, a majority of HBV-infected individuals are not able to access adequate health care owing to numerous barriers. Objective This study aimed to assess the efficacy of a newly developed mobile texting app (HepTalk) in overcoming these barriers and improving patient engagem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Patients who are more knowledgeable about patient safety are more likely to participate in patient safety activities and their care. 20 , 21 , 27 In addition, programmes and various other patient safety education resources such as leaflets, patient safety videos or patient‐safety campaigns targeting patients positively affect their attitudes towards and behaviours of patient participation. 10 , 27 , 45 In this study, we developed a mobile application to encourage health consumers' participation in patient safety activities by providing information on patient participation and actionable tools for participation in their care process, and evaluated the effects of the mobile application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients who are more knowledgeable about patient safety are more likely to participate in patient safety activities and their care. 20 , 21 , 27 In addition, programmes and various other patient safety education resources such as leaflets, patient safety videos or patient‐safety campaigns targeting patients positively affect their attitudes towards and behaviours of patient participation. 10 , 27 , 45 In this study, we developed a mobile application to encourage health consumers' participation in patient safety activities by providing information on patient participation and actionable tools for participation in their care process, and evaluated the effects of the mobile application.…”
Section: Discussionmentioning
confidence: 99%
“…To broaden the range of patients who can participate in their care process to prevent errors and lead to better health outcomes, it is necessary to expand the research population to include health consumers who visit the hospital. Some studies have conducted interventions for patient participation and evaluated their effectiveness 10,20,21 . However, these studies were more focused on hospitalized patients 20 or patients with a certain disease 21 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one study showed limited maintenance of behavior changes once the SMS text messaging intervention ceased [17]. SMS text messaging programs have also been utilized effectively in many other medical settings including diabetes [18], maternal health [19], hepatitis B [20], and smoking cessation [21].…”
Section: Introductionmentioning
confidence: 99%